PENGARUH PENERAPAN KONSEP TEAM WORK DAN BUDAYA ORGANISASI TERHADAP KINERJA PERAWAT (Studi Pada Rumah Sakit Umum Daerah Sunan Kalijaga Kabupaten Demak) - Rahma, Audina; Mas’ud, Fuad (Faculty of Economics and Business Diponegoro University, 2016)
This study aimed to analyze the effect of team work and organizational culture on performance of nurses (Studies in the General Hospital of Sunan Kalijaga Demak). Variables (Independent) of this research is teamwork (X1) and organizational culture (X2). While the Bound Variable (Dependent) in this study was the performance of nurses denoted Y. The population in this study were nurses civil servants who work in hospitals LOVE consisting of 162 people, 162 nurses were then selected by criteria have been working for 2 years and a nurse who was PNS, so we get a sample of 98. the data collection methods used in this study is a questionnaire using Likert scale with interval 1-5. The analytical method used to test data quality, classic assumption test and test hypotheses with SPSS version 20.0. The hypothesis of this study is H1 = Teamwork positive effect on performance, H2 = Organizational culture positive effect on performance. The analysis showed that the organizational culture of team work and positive influence on the performance of nurses. The results of the simultaneous test obtained F value of 7.883, the significant difference between the team work (X1) and organizational culture (X2) on the performance of nurses (Y) and vice versa. The results of hypothesis testing variables have the team work t count equal to 3.117 with a significance level of 0.002 <0.05. Thus H1 accepted, so it can be said that team work and significant positive effect on the performance of nurses. Hypothesis test results have organizational culture variable t count equal to 2,165 with significance level of 0.033 <0.05. Thus H2 is accepted, it may be said that the organizational culture positive and significant effect on the performance of nurses.